2014
DOI: 10.1007/s00248-014-0516-0
|View full text |Cite
|
Sign up to set email alerts
|

Different Continuous Cropping Spans Significantly Affect Microbial Community Membership and Structure in a Vanilla-Grown Soil as Revealed by Deep Pyrosequencing

Abstract: In the present study, soil bacterial and fungal communities across vanilla continuous cropping time-series fields were assessed through deep pyrosequencing of 16S ribosomal RNA (rRNA) genes and internal transcribed spacer (ITS) regions. The results demonstrated that the long-term monoculture of vanilla significantly altered soil microbial communities. Soil fungal diversity index increased with consecutive cropping years, whereas soil bacterial diversity was relatively stable. Bray-Curtis dissimilarity cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
141
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 227 publications
(184 citation statements)
references
References 52 publications
39
141
3
1
Order By: Relevance
“…Vanilla growth had been almost entirely decimated in this field [3]. The field was located in the Spice and Beverage Research Institute of the Chinese Academy of Tropical Agricultural Sciences, Xinglong, Hainan Province (110˚20'E, 18˚73'N); the soil contained 35.9 g•kg −1 of organic matter, 82.52 mg•kg −1 of available N, 336.36 mg•kg −1 of available P (Olsen), and 98.85 mg•kg −1 of available K (NH 4 OAc).…”
Section: Pot Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Vanilla growth had been almost entirely decimated in this field [3]. The field was located in the Spice and Beverage Research Institute of the Chinese Academy of Tropical Agricultural Sciences, Xinglong, Hainan Province (110˚20'E, 18˚73'N); the soil contained 35.9 g•kg −1 of organic matter, 82.52 mg•kg −1 of available N, 336.36 mg•kg −1 of available P (Olsen), and 98.85 mg•kg −1 of available K (NH 4 OAc).…”
Section: Pot Experimental Designmentioning
confidence: 99%
“…vanilla, causes heavy economic losses in numerous vanilla-planting regions [7]. On long-term monoculture vanilla plantations, this disease has spread widely; the plant symptoms have worsened and the soil microbial community structure is out of balance [3]. In addition, the intensive growth of vanilla requires a very high consumption of chemical fertilizers and pesticides, resulting in serious environmental and food safety problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Navarrete et al [7] reported taxonomic and functional adaptations in soil microbiome after deforestation in the Amazon region and these adaptations typically result in increased soil fertility. Other agricultural practices, such as logging [43], tillage [44] and cropping systems [45,46], also play roles in effecting structural and functional changes in soil microbiome that lead to changes in soil functions. As many of the discussed agricultural management practices have been implemented for decades with success, recent efforts in understanding their effects on soil microbiota composition would enable rational engineering of the soil microbiome to optimize these practices for improved crops.…”
Section: Engineering Of Soil Microbiomementioning
confidence: 99%
“…Agricultural management Soil Organic farming, changing land usage, logging, tillage, cropping [7,[41][42][43][44][45][46] Improve soil fertility • Alter structure and function of soil microbiome;…”
Section: Examples Purposes Remarksmentioning
confidence: 99%